Validation of the Antioxidant and Enzyme Inhibitory Potential of Selected Triterpenes Using In Vitro and In Silico Studies, and the Evaluation of Their ADMET Properties - Nilufar Z. Mamadalieva (MDPI AG, 2021)
The antioxidant and enzyme inhibitory potential of fifteen cycloartane-type triterpenes’ potentials were investigated using different assays. In the phosphomolybdenum method, cycloalpioside D (6) (4.05 mmol TEs/g) showed the highest activity. In 1,1-diphenyl-2-picrylhydrazyl (DPPH*) radical and 2,2′-azino-bis(3-ethylbenzothiazoline)-6-sulfonic acid (ABTS) cation radical scavenging assays, cycloorbicoside A-7-monoacetate (2) (5.03 mg TE/g) and cycloorbicoside B (10) (10.60 mg TE/g) displayed the highest activities, respectively. Oleanolic acid (14) (51.45 mg TE/g) and 3-O-β-d-xylopyranoside-(23R,24S)-16β,23;16α,24-diepoxycycloart-25(26)-en-3β,7β-diol 7-monoacetate (4) (13.25 mg TE/g) revealed the highest reducing power in cupric ion-reducing activity (CUPRAC) and ferric-reducing antioxidant power (FRAP) assays, respectively. In metal-chelating activity on ferrous ions, compound 2 displayed the highest activity estimated by 41.00 mg EDTAE/g (EDTA equivalents/g). The tested triterpenes showed promising AChE and BChE inhibitory potential with 3-O-β-d-xylopyranoside-(23R,24S)-16β,23;16α,24-diepoxycycloart-25(26)-en-3β,7β-diol 2′,3′,4′,7-tetraacetate (3), exhibiting the highest inhibitory activity as estimated from 5.64 and 5.19 mg GALAE/g (galantamine equivalent/g), respectively. Compound 2 displayed the most potent tyrosinase inhibitory activity (113.24 mg KAE/g (mg kojic acid equivalent/g)). Regarding α-amylase and α-glucosidase inhibition, 3-O-β-d-xylopyranoside-(23R,24S)-16β,23;16α,24-diepoxycycloart-25(26)-en-3β,7β-diol (5) (0.55 mmol ACAE/g) and compound 3 (25.18 mmol ACAE/g) exerted the highest activities, respectively. In silico studies focused on compounds 2, 6, and 7 as inhibitors of tyrosinase revealed that compound 2 displayed a good ranking score (−7.069 kcal/mole) and also that the ΔG free-binding energy was the highest among the three selected compounds. From the ADMET/TOPKAT prediction, it can be concluded that compounds 4 and 5 displayed the best pharmacokinetic and pharmacodynamic behavior, with considerable activity in most of the examined assays.